Sipuleucel-T and Androgen Receptor-Directed Therapy for Castration-Resistant Prostate Cancer: A Meta-Analysis - Renliang Yi; Baoxin Chen; Peng Duan; Chanjiao Zheng; Huanyu Shen; Qun Liu; Chen Yuan; Weilin Ou; Zhiheng Zhou (Journal of Immunology Research)
New treatments, such as sipuleucel-T and androgen receptor- (AR-) directed therapies (enzalutamide (Enz) and abiraterone acetate (AA)), have emerged and been approved for the management of castration-resistant prostate cancer (CRPC). There are still debates over their efficacy and clinical benefits. This meta-analysis aimed to investigate the efficacy and safety of sipuleucel-T and AR-directed therapies in patients with CRPC. RevMan 5.1 was used for pooled analysis and analysis of publication bias. Seven studies were included in the meta-analysis, with three studies in sipuleucel-T (totally 737 patients, 488 patients in treatment group, and 249 patients in placebo group) and four in AR-directed therapies (totally 5,199 patients, 3,015 patients in treatment group, and 2,184 patients in placebo group). Treatment with sipuleucel-T significantly improved overall survival in patients with CRPC and was not associated with increased risk of adverse event of grade ≥3 (p>0.05). However, treatment with sipuleucel-T did not improve time-to-progression and reduction of prostate-specific antigen (PSA) level ≥50% was not significantly different from that with placebo. AR-directed therapies significantly improved overall survival in patients with CRPC and improved time-to-progression and reduction of PSA level ≥50%. AR-directed therapies did not increase risk of adverse event of grade ≥3 (p>0.05).